2018
DOI: 10.1186/s12915-018-0607-3
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of mitochondrial TAT translocases illustrates the loss of bacterial protein transport machines in mitochondria

Abstract: BackgroundBacteria and mitochondria contain translocases that function to transport proteins across or insert proteins into their inner and outer membranes. Extant mitochondria retain some bacterial-derived translocases but have lost others. While BamA and YidC were integrated into general mitochondrial protein transport pathways (as Sam50 and Oxa1), the inner membrane TAT translocase, which uniquely transports folded proteins across the membrane, was retained sporadically across the eukaryote tree.ResultsWe h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 75 publications
0
25
0
Order By: Relevance
“…In proteobacteria, the minimal active TAT system consists of three proteins, TatA, TatB, and TatC [168]. Orthologs of TatA and TatC, encoded by mtDNA, have a scattered distribution among eukaryotes, but whether these proteins constitute an active system in the organelle is not clear [169]. In plants, whose mitochondrial genomes encode only TatC, a TatB but apparently not TatA ortholog is encoded in the nuclear genome, and a functional TatB-TatC complex has been proposed in this case [170].…”
Section: Translocase Of the Inner Mitochondrial Membrane Tim22mentioning
confidence: 99%
“…In proteobacteria, the minimal active TAT system consists of three proteins, TatA, TatB, and TatC [168]. Orthologs of TatA and TatC, encoded by mtDNA, have a scattered distribution among eukaryotes, but whether these proteins constitute an active system in the organelle is not clear [169]. In plants, whose mitochondrial genomes encode only TatC, a TatB but apparently not TatA ortholog is encoded in the nuclear genome, and a functional TatB-TatC complex has been proposed in this case [170].…”
Section: Translocase Of the Inner Mitochondrial Membrane Tim22mentioning
confidence: 99%
“…The TatC protein is an essential component of the Tat system. In a previous study, TatC gene was identified in the mitochondrial genomes of oomycetes [42]. To determine the function of ymf16 gene, its predicted protein sequences from the 10…”
Section: Protein Coding Gene Contents In the Mitochondrial Genomes Ofmentioning
confidence: 99%
“…It also encodes named protein-coding genes commonly found in green algae (Table 3, S3). This does include some genes that are less common in Chlorophyta mitochondrial genomes: nad10, which is absent from the mtDNA of sequenced land plants and many green algae (Mower et al, 2012), and tatC, a gene encoding a component of the inner membrane TAT translocase responsible for transporting folded proteins across the membrane in bacteria but whose function in mitochondria remains unclear (Carrie et al, 2016;Petrů et al, 2018).…”
Section: Ostreobium Mitochondrial Genomementioning
confidence: 99%